The Contribution of Common Genetic Variation to Nicotine and Cotinine Glucuronidation in Multiple Ethnic/Racial Populations - Yesha Patel; Daniel O. Stram; Lynne R. Wilkens; Sung-Shim L. Park; Brian E. Henderson; Loı̈c Le Marchand; Christopher A. Haiman; Sharon E. Murphy (2014)
The lung cancer risk of smokers varies by race/ethnicity even after adjustment for smoking. Evaluating the role of genetics in nicotine metabolism is likely important in understanding these differences, as disparities in risk may be related to differences in nicotine dose and metabolism.We conducted a genome-wide association study in search of common genetic variants that predict nicotine and cotinine glucuronidation in a sample of 2,239 smokers (437 European Americans, 364 African Americans, 453 Latinos, 674 Japanese Americans, and 311 Native Hawaiians) in the Multiethnic Cohort Study. Urinary concentration of nicotine and its metabolites were determined.Among 11,892,802 variants analyzed, 1,241 were strongly associated with cotinine glucuronidation, 490 of which were also associated with nicotine glucuronidation (P < 5×10(-8)). The vast majority were within chromosomal region 4q13, near UGT2B10. Fifteen independent and globally significant SNPs explained 33.2% of the variation in cotinine glucuronidation, ranging from 55% for African Americans to 19% for Japanese Americans. The strongest single SNP association was for rs115765562 (P = 1.60 × 10(-155)). This SNP is highly correlated with a UGT2B10 splice site variant, rs116294140, which together with rs6175900 (Asp67Tyr) explains 24.3% of the variation. The top SNP for nicotine glucuronidation (rs116224959, P = 2.56 × 10(-43)) was in high LD (r(2) = 0.99) with rs115765562.Genetic variation in UGT2B10 contributes significantly to nicotine and cotinine glucuronidation but not to nicotine dose.The contribution of genetic variation to nicotine and cotinine glucuronidation varies significantly by racial/ethnic group, but is unlikely to contribute directly to lung cancer risk.